Combined pinch and mathematical programming method for coupling integration of reactor and threshold heat exchanger network. (15th August 2020) - Zhang, Di; Lv, Donghui; Yin, Changfang; Liu, Guilian
Abstract: A combined Pinch and Mathematical Programming Methodology is proposed to systematically integrate and optimize reactor and Threshold Heat Exchanger Network (HEN). With the reaction kinetics, mass balance and energy balance considered, the energy consumption of the Threshold HEN is analyzed based on the Composite Curves. Relations among the utility consumption of HEN, conversion and reactor temperature are deduced. With the Minimum Temperature Approach taken as a variable and both capital and utility cost considered, a Mixed Integer Nonlinear Programming (MINLP) model is developed to integrate HEN and reactor. Based on this model, the maximum net annual revenue and utility consumptions at different conversions can be identified, as well as the corresponding inlet and outlet temperature of reactors and Minimum Temperature Approach. A duty-annual revenue-conversion-temperature ( Q ˙ - Y NAR - X - T ) diagram is constructed to illustrate their variation, and intuitively target the optimal conversion and corresponding parameters. A steam-reforming process is studied by the proposed method. The optimal conversion of the reactor is identified to be 0.84, and the net annual revenue can be increased by 27.82% after the optimization. Highlights: A combined Pinch and Mathematical Programming method is proposed. Reactor and Threshold HEN are integrated considering reaction kinetics, mass and energy balance. A MINLP model is developed with the Minimum Temperature Approach (Δ T min ) taken as a variable. Diagram is built to target the optimal conversion, Δ T min and reactor parameters. The net annual revenue of the steam-reforming process increases by 27.82% after optimization.